Case Report: Vertical muscle-sparing latissimus dorsi flap in the reconstruction of chronic radiation-induced chest wall ulcers after breast cancer surgery: a case series - Han, Sung Joon; Kim, Junghee; Kim, Sunje; Ha, Yooseok (Frontiers in Surgery, 2024)
Radiation therapy, a standard postoperative treatment for breast cancer, can lead to chronic ulcers owing to compromised tissue healing. Accordingly, flap surgery using healthy tissues is essential for aesthetic and functional recovery. Although various flap techniques exist, each has its own drawbacks. This study introduces the vertical muscle-sparing latissimus dorsi flap as a superior alternative due to its comparative operative efficiency and tissue preservation. Case Report: Two female patients aged 60 and 59 years with histories of breast cancer in their left breast treated with radiotherapy presented with chronic ulcers. The first patient had a 4x5 cm defect infiltrating the pleural space, while the second had a 15x9 cm defect after thoracic surgery for a bronchopleural fistula. In both cases, debridement was followed by reconstruction using a vertical muscle-sparing latissimus dorsi flap, thereby avoiding the need to change the patient's position and repeated draping during surgery. Both patients showed good postoperative recovery without significant complications. Results: The vertical muscle-sparing latissimus dorsi flap resulted in better adhesions and functional outcomes due to shorter surgical duration. Conclusion: The vertical muscle-sparing latissimus dorsi flap is an effective and efficient method for reconstructing radiation-induced chest wall ulcers in patients with breast cancer. Its application in the presented cases highlights its potential as a preferred option in similar clinical scenarios.